The Effect of Diabetes Mellitus Severity on Foot & Ankle Burn Recovery - Sheldon A. McCown; Elliot T. Walters; Alen Palackic; Camila Franco-Mesa; Ashton R. Davis; Phillip H. Keys; Juquan Song; Steven E. Wolf (European Burn Journal)
Background: Diabetic patients often present with complex limb pathology, resulting in impaired sensation in the distal extremities making tactile injuries such as burns difficult to notice. We posit that poorly controlled diabetes mellitus, evidenced by increasing elevations in hemoglobin A1c, is associated with delayed wound healing and increased complications in burn patients. Methods: The TriNetX Network, a database of 89 million patients across the U.S., was queried for diabetic patients with foot and ankle burns. Patients were divided into four groups based on A1c: properly controlled (<7%), moderately controlled (7–9%), poorly controlled (>9%), and propensity-matched non-diabetic controls. Evaluated outcomes included split-thickness skin grafting, infections, amputations, acute kidney failure (AKF), and mortality within one month of the burn. Results: When comparing the poorly controlled A1c cohort with the properly controlled and moderately controlled A1c cohorts, we found a significant increase in amputations (p = 0.042) and cutaneous infections (p = 0.0438), respectively. When evaluating non-diabetics to diabetic patients, significantly increased rates of amputations (p < 0.0001), cutaneous infections (p = 0.0485), systemic infections (p = 0.0066), and AKF (p = 0.0005) were noted in the latter. Conclusions: Poorly controlled diabetes shows a significant correlation with increased complications following foot and ankle burns, including amputations, infections, and AKF.